Evaluation of serum carbohydrate antigen 19-9 as a diagnostic marker for pancreatic malignancy - Ullah, A.K.M. Ahsan; Ahmed, S. M. Ferdous; Chowdhury, A. S. M. Lokman Hossain; Mohammed, Saad; Haque, M. Mozammel; Rana, Abunur M. Masud (International Surgery Journal, 2020)
Background: Carbohydrate antigen (CA) 19-9 is considered as a tumor marker in biliary-pancreatic malignancy. Though a high level may indicate the presence of a malignant disorder, it may rise even in benign condition. Similarly, the value may be normal even in malignant condition. Methods: An observational comparative study was conducted in the Department of Surgery of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from 01 June 2016 to 31 May 2017 to find out the sensitivity and specificity of CA 19-9 as a tumor marker in pancreatic malignancy in our perspective and to find out a cut-off value of CA 19-9 which might prove as a definitive indication of pancreatic malignancy. Results: The study shows when the cut off value of CA 19-9 is 37 U/ml. The sensitivity, specificity, positive and negative predictive values (PPV and NPV) were 77.8%, for all four characteristics respectively. But if the serum CA 19-9 threshold used to diagnose pancreatic cancer was raised to 100 and 120, sensitivity decreased to 72.2% and 66.7% and NPV decreased to 76.2% and 73.9% respectively. However, specificity increased to 88.9% and 94.4% and PPV increased to 86.7% and 92.3% respectively. Conclusions: Serum CA 19-9 level may be considered as an important determinant in the diagnosis of malignant pancreatic diseases and to assess the resectability of the lesions preoperatively, but other adjuncts are necessary in the overall management of pancreatic diseases.